Modelling Longitudinal Survey Response: The Experience of the HILDA Survey - Wooden, M; Watson, N (Melbourne Institute of Applied Economic and Social Research, 2006)
Like all sample surveys, longitudinal (or panel) surveys are affected by unit non-response. A distinctive feature of longitudinal surveys, however, is that non-response is not a one-off event and tends to accumulate over time as further waves of interviewing are conducted. Longitudinal surveys also face the problems of tracking sample members who relocate and of dealing with the respondent fatigue that is associated with repeated survey participation (Laurie, Smith and Scott, 1999).
HILDA Project Discussion Paper Series
Keywords: Surveys and Survey Methodology -- Survey response; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Survey response; Surveys and Survey Methodology